Information Utilization for Weedicide Usage among the Paddy Farmers in Eravur Pattu DS Division of Batticaloa District - Selvarajah, V.; Geretharan, T. (SEUSL, 2013)
Information is an essential factor in the practice of farming and it is the foundation of extension service delivery. The modern agrochemical companies generally provide similar weedicide products with different brand names. Owing to this, farmers race difficulties while selecting relevant weedicides. They need appropriate information in order to select exact weedicides. In this regard, a study was conducted to find out the information utilization and weedicide usage among the paddy farmers in the Eravur Pattu Divisional Secretariat division of Batticaloa district Hundred number of paddy farmers were randomly selected for this study. Questionnaire survey was used as the primary data collection method. Secondary data were collected from published sources. The study reveals that, obtaining higher yield was the main reason for the usage of weedicides by the paddy farmers to control weeds in their farm land, followed by severe weed attack. Regarding the information related to weedicide application, paddy farmers in the Eravur Pattu area frequently got information on weedcide application rate from the Extension personnel. But, the selection of agrochemical traders to purchase weedicide was mainly determined by the farmers themselves. Significant associations were observed between fanning experience and purchasing decision based on Extension agents and also farming type and purchasing decision based on Extension agents. It was recommended mat Extension agents should intensify their efforts in educating and advising farmers how to utilize the relevant information to decide relevant weedicides.
Keywords: Extension agents; Information; Paddy farmers; Weedicides